Effect of synthesized ump surfactant for emulsification and stabilization of water-incrude oil emulsions - Nour, Abdurahman Hamid; Humadi, Magdi Ahmed (2021)
With the increasing energy crisis and the drive to reduce CO 2emissions, universities and industries are challenged to find new technologies in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. In the conventional combustion process, fuel is combined with air and turned. The result is carbon dioxide, water vapour and heavy oxides of Nitrogen, which are a prime cause of chemical smog. If water could largely replace air as a source of oxygen in combustion, this would avoid the large amounts of Nitrogen introduced by air. And thus eliminate much of the noxious Nitrogen oxides. This invention makes the replacement of air as source of Oxygen by water (30%).The invention is highly a new contribution for energy sources and highly reduces the emission problems cause by Nitrogen Oxides.